Awareness about Life-style Modication in Hypertensive Patients Residing in Natore District, Bangladesh (Ibrahim Cardiac Medical Journal, 2019)
Objective: For better control of hypertension, behavior (knowledge, attitude and practice) of hypertensive patients about life-style change is essential. This study was done to determine the level of knowledge, attitude and practice of hypertensive patients regarding life-style change needed to control of hypertension.Methods: The present cross-sectional study was conducted in Natore General Hospital, Natore over a period of 4 months from September to December, 2015. A total of 50 adult hypertensive patients suffering from the disease for at least six months were included in the study. Of them 20 were selected from patients attending at the Outpatient Department of Medicine, Natore General Hospital and 30 were selected by snowballing. Data were collected using a semi-structured questionnaire and the levels of knowledge and practice status were measured on Likert Scale (0-4). Score ‘1’ was assigned for each correct answer and score ‘0’ for each wrong answer, except for two knowledge-related questions where highest score was ‘2’ and the lowest was ‘0’. As there were more than one question in assessing respondents’ perception and practice, combined scores were used to measure the intended behaviour.Results: The result showed that about two-thirds (66%) of the respondents lie between 4th and 5th decades of life with mean age being 48.4 years (range: 17 – 80 ears). Male to female ratio was roughly 1:1. Majority (96%) of the respondents was married. Primary level educated formed about one-third (32%) of the respondents followed by HSC (20%), graduation (18%) and illiterate (16%). Nearly half (46%) of the respondents was poor. Seventy percent of the respondents’ blood pressure was beyond control at the time of interview with mean systolic and diastolic blood pressures being 140 and 92 mmHg respectively. More than half (54%) of the respondents’ duration of hypertension was < 5 years with median duration being 3 years. Over one-quarter (28%) was adequately aware and two-thirds (68%) were partially aware of lifestyle modification and most (88%) of the respondents’ source of information was doctor. Although majority (84%) was informed of life-style change from their doctors, only 28.6% of them considered those advices to be adequate to bring about effective change in their life-style. Majority (92%) held the view that additional salt to be avoided followed by smoking cessation or tobacco chewing (88%), diet control (84%) and having regular exercise (82%). A substantial proportion (72%) also put emphasis to weight reduction. In terms of practice, over two-thirds (70%) adopted change in their life-style to control blood pressure. Of them 20(57.1%) were practicing diet control, another 20(57.1%) avoiding added salt with meals and 10(28.5%) quitted smoking for reducing the chance of having heart attack or stroke in future. Ten (20%) respondents were used to smoking at the time of interview. Of them 7(70%) intended to give up the habit. Half (52%) of the respondents took exercise but the rate of performing regular exercise (5 days in a week) was only 19.3%. Those who were not used to taking exercise, 16.7% of them told that they did not have spare time to have exercise, about 30% told that the role of exercise on blood pressure control was not known to them, another 30% tried but failed to continue and 20.8% were reluctant to take exercise. More than half (56%) of the respondents’ level of knowledge was satisfactory, followed by 30% more or less satisfactory and 14% poor. However, about one-third (32%) of the respondents’ practice level was satisfactory, 34% more or less satisfactory, 24% poor, 8% very poor and only 2% highly satisfactory.Conclusion: The knowledge level of hypertensive patients about their life-style change is far below the desired level. The practice level is even low meaning that not all the respondents having knowledge about life-style modification translated the same into practice This indicates that there lies a gap between perception & practice which act as a barrier to motivation.Ibrahim Card Med J 2017; 7 (1&2): 23-30